The effectiveness of educational intervention program on knowledge of BSE among secondary school girls in Seremban, Negeri Sembilan - Norhayati Mohd Zain,; Nur Anis Izzati Che Mut,; Noor Hidayah Abu Bakar,; Izdihar Kamal,; Siti Aishah Abdullah Suhaimi,; Nurul Mawaddah Mohammad,; Rosmah Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Breast Self-Examination (BSE) is important to be introduced to secondary school girls in order to develop a positive health behavior. Limited attention has been given on knowledge among school girls. Hence, this study was conducted to determine the effectiveness of educational intervention program on knowledge of BSE among secondary school girls in Seremban, Negeri Sembilan. A cross-sectional study was conducted among 502 volunteered secondary school girls using pre and post self-administered validated questionnaire. The mean (SD) age of the participants was 14.9 (± 0.1) years. Majority of the participants were Malays (87.1%). Pre-intervention educational program revealed that 91% of the participants had poor knowledge whereas 9% had good knowledge on BSE. Post-educational intervention program showed that knowledge has increased by 33.4% and percentage for ‘poor’ knowledge reduced by 33.4% from pre-intervention scored (p < 0.001). There was no significant difference on knowledge of BSE among participants with and without family history of breast cancer (p = 0.204). Health campaign was the top source of information to gain knowledge related to BSE prior (56.6%) and after (90.2%) the intervention program (p < 0.001). Thus, the educational intervention program was found to be effective method to improve the knowledge on BSE among secondary school girls.